Sustainable energy for a resilient future: proceedings of the 14th International Conference on Sustainable Energy Technologies - Rodrigues, Lucélia Taranto (University of Nottingham, 2016)
Volume I, 898 pages, ISBN 9780853583134 Energy Technologies & Renewables Session 1: Biofuels & Biomass Session 5: Building Energy Systems Session 9: Low-carbon/ Low-energy Technologies Session 13: Biomass Systems Session 16: Solar Energy Session 17: Biomass & Biofuels Session 20: Solar Energy Session 21: Solar Energy Session 22: Solar Energy Session 25: Building Energy Technologies Session 26: Solar Energy Session 29: Low-carbon/ Low-energy Technologies Session 32: Heat Pumps Session 33: Low-carbon/ Low-energy Technologies Session 36: Low-carbon/ Low-energy Technologies Poster Session A Poster Session B Poster Session C Poster Session E